Electronic and magnetic properties of X2YZ and XYZ Heusler compounds: a comparative study of density functional theory with different exchange-correlation potentials. (29th July 2016) - Rai, D P; Sandeep,; Shankar, A; Sakhya, Anup Pradhan; Sinha, T P; Khenata, R; Ghimire, M P; Thapa, R K
Abstract: The electronic and magnetic properties of Heusler compounds X2 YZ and XYZ (X = Co, Ni, Pt, Fe; Y = Mn, Cr, Vi; Z = Al, Sb, Ga) are investigated by using the density functional theory with generalized gradient approximation (GGA), GGA plus U (LSDA+U), and modified Becke−Johnson (mBJ) exchange potential. It is found that the half-metallic gaps are generally widened reasonably by LSDA+U and mBJ as compared to the conventional GGA. For the Co-based Heusler compounds the inclusion of U in GGA leads to a larger minority band gap while it is destroyed for Fe2 VAl and NiMnSb. The magnetic properties of Co2 VSi and Co2 VSn are well defined within LSDA+U and mBJ with an exact integer value of magnetic moment. The band gaps of Fe2 VAl and CoMnSb given by mBJ are in good agreement with the available experimental data of x-ray absorption spectroscopy. Except for the reasonably larger band gap, the mBJ band structure is almost same as that of GGA but is remarkably different from that of LSDA+U.